Synthesis and Characterization of New Palladium(II) Thiosemicarbazone Complexes and Their Cytotoxic Activity against Various Human Tumor Cell Lines. (11th December 2013) - Hernández, Wilfredo; Paz, Juan; Carrasco, Fernando; Vaisberg, Abraham; Spodine, Evgenia; Manzur, Jorge; Hennig, Lothar; Sieler, Joachim; Blaurock, Steffen; Beyer, Lothar
Abstract : The palladium(II) bis-chelate complexes of the type [Pd(TSC 1-5 )2 ] (6–10 ), with their corresponding ligands 4-phenyl-1-(acetone)-thiosemicarbazone, HTSC 1 (1 ), 4-phenyl-1-(2′-chloro-benzaldehyde)-thiosemicarbazone, HTSC 2 (2 ), 4-phenyl-1-(3′-hydroxy-benzaldehyde)-thiosemicarbazone, HTSC 3 (3 ), 4-phenyl-1-(2′-naphthaldehyde)-thiosemicarbazone, HTSC 4 (4 ), and 4-phenyl-1-(1′-nitro-2′-naphthaldehyde)-thiosemicarbazone, HTSC 5 (5 ), were synthesized and characterized by elemental analysis and spectroscopic techniques (IR and 1 H- and 13 C-NMR). The molecular structure of HTSC 3, HTSC 4, and [Pd(TSC 1 )2 ] (6 ) have been determined by single crystal X-ray crystallography. Complex 6 shows a square planar geometry with two deprotonated ligands coordinated to P d II through the azomethine nitrogen and thione sulfur atoms in a cis arrangement. The in vitro cytotoxic activity measurements indicate that the palladium(II) complexes (I C 50 = 0.01 –9.87 μ M) exhibited higher antiproliferative activity than their free ligands (I C 50 = 23.48 –70.86 and >250 μ M) against different types of human tumor cell lines. Among all the studied palladium(II) complexes, the [Pd(TSC 3 )2 ] (8 ) complex exhibited high antitumor activity on the DU145 prostate carcinoma and K562 chronic myelogenous leukemia cells, with low values of the inhibitory concentration (0.01 and 0.02 μ M, resp.).